2001
DOI: 10.1002/cm.1028
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of flagellar dynein function in a Chlamydomonas actin/dynein‐deficient mutant upon introduction of muscle actin by electroporation

Abstract: Flagellar and ciliary inner-arm dyneins contain actin as a subunit; however, the function of this actin subunit remains unknown. As a first step toward experimental manipulation of actin in dynein, we developed a method for introducing exogenous actin into Chlamydomonas cells by electroporation. A non-motile mutant, ida5oda1, lacking inner-arm dyneins due to the absence of conventional actin, was electroporated in the presence of rabbit skeletal muscle actin. About 20% of the electroporated cells recovered mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…Those motile cells displayed rhodamine fluorescence in their flagella (data not shown). These observations are essentially the same as reported by Hayashi et al (2001). …”
Section: Introduction Of Fluorescently Labeled Actin Into Ida5oda1 Bysupporting
confidence: 92%
See 4 more Smart Citations
“…Those motile cells displayed rhodamine fluorescence in their flagella (data not shown). These observations are essentially the same as reported by Hayashi et al (2001). …”
Section: Introduction Of Fluorescently Labeled Actin Into Ida5oda1 Bysupporting
confidence: 92%
“…Upon incorporation of exogenous actin, it became motile due to the recovery of missing inner arm dyneins. As in our previous study (Hayashi et al, 2001), electroporation at ~1200 V/cm was found to be optimal, where about 50% of total cells were killed and 10-20% of surviving cells regained motility. Those motile cells displayed rhodamine fluorescence in their flagella (data not shown).…”
Section: Introduction Of Fluorescently Labeled Actin Into Ida5oda1 Bysupporting
confidence: 79%
See 3 more Smart Citations